PENGEMBANGAN APLIKASI PROGRAM E-BANGKIT BERBASIS ANDROID - Noorhapizah, Noorhapizah; Prihandoko, Yogi; Agus Rifani Syaifuddin; Diani Ayu Pratiwi; Mubarok (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The e-BANGKIT application is a digital innovation developed under the BANGKIT program to enhance efficiency and facilitate the implementation of the Pancasila Student Profile Strengthening Project (P5), based on local wisdom in wetland environments at the elementary school level, through the integration of Android-based technology. This study aims to: (1) develop the e-BANGKIT application as a digital innovation for the P5 program in elementary schools within wetland areas, and (2) evaluate the effectiveness of the e-BANGKIT application in supporting the implementation of P5 in those schools. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results show that the product underwent validation by subject matter experts, media experts, and language experts. Product trials were conducted to measure teacher and student responses in three elementary schools. Data were collected using observation sheets, questionnaires, and documentation. Validation results indicated average scores of 84.6% from subject matter experts, 89.5% from media experts, and 90% from language experts. Teacher questionnaires yielded a score of 82.8%, while a limited trial with fifth-grade students resulted in a score of 94.8%. These findings suggest that the e-BANGKIT application is feasible, practical, and effective.